Implementasi Model Pembelajaran Berdiferensiasi pada Kurikulum Merdeka dalam Membangun Motivasi dan Aktivitas Belajar Siswa Sekolah Dasar (Siswa SD Negeri 1 Sumberjo Kulon Kecamatan Ngunut Kabupaten Tulungagung) - Yuliana, Dewi; Subiyantoro, Hari; Ana, Ria Fajrin Rizqi (Efektor, 2024)
Learning using a differentiated learning model is an effective solution to facilitate the diversity of student characteristics in learning. This research aims to describe the planning of differentiated learning model in building motivation and learning activities of students, describe the implementation of differentiated learning model in building motivation and learning activities of students, and describe the evaluation of differentiated learning model in building motivation and learning activities of students of SD Negeri 1 Sumberjo Kulon Ngunut Subdistrict. The research method is qualitative research. Data collection techniques using observation, interviews and documentation. Data analysis techniques use variable data methods, data presentation and conclusion drawing. The results of the research: 1) The planning of the differentiated learning model includes mapping student learning profiles using initial diagnostic assessment and observation results written on the teaching module, the activity plan refers to the reflection of previous learning activities so that learning activities and motivation are increasingly built. 2) Implementation of differentiated learning model in building students' motivation and learning activities is carried out by using content differentiation, process and product differentiation. 3) Evaluation of differentiated learning model in building students' motivation and activity is carried out by conducting assessment and reflection of teachers and students. The conclusion of this research is that the implementation of differentiated learning model if implemented optimally can build students' motivation and learning activities.